"The Game Was Ruined For Me There:" Examining the Mental Health Byproducts of the Transfer Portal and NIL on Student-Athletes - Ethan Madden; Brendan O'Hallarn (Bowling Green State University, 2024)
Two rule changes have brought seismic changes to collegiate sports in the United States-the right for college athletes to monetize their Name, Image, and Likeness (NIL), and the Transfer Portal for athletes looking to switch schools. Qualitative interviews with 16 college athletes, explored the mental health byproducts of these new athlete opportunities. The interviews suggest that many athletes are hesitant to participate in NIL due to a lack of guidance. The study also found that college athletes believe entering the Transfer Portal to be a highly stressful experience, comparing the process to being recruited out of high school. However, the accessibility of the Transfer Portal also helps students leave situations that are negatively impacting their mental health faster and easier than before. Since college athletes are a highly at-risk demographic of college athletes for mental health issues, their first-hand perspective can help on-campus staff and administrators have a better understanding of what is needed to give collegiate athletes the best possible experience to learn and develop as students and citizens.